2021
DOI: 10.1002/cmdc.202100332
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Strategies to Selectively Target mTOR Kinase

Abstract: Dysregulation of the mechanistic target of rapamycin (mTOR) pathway is implicated in cancer and neurological disorder, which identifies mTOR inhibition as promising strategy for the treatment of a variety of human disorders. First-generation mTOR inhibitors include rapamycin and its analogues (rapalogs) which act as allosteric inhibitors of TORC1. Structurally unrelated, ATP-competitive inhibitors that directly target the mTOR catalytic site inhibit both TORC1 and TORC2. Here, we review investigations of chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 136 publications
(226 reference statements)
0
7
0
Order By: Relevance
“…We next examined whether the observed effect of BGT226 is due to its inhibitory activity against ATM or mTOR/PI3K. We compared the effect of BGT226 with another PI3K/mTOR inhibitor VS-5584 that has similar or stronger effect in inhibiting PI3K and mTOR but no inhibition against ATM ( 37 ). We found that BGT226 but not VS-5584 sensitizes growth inhibition of cancer cells in response to NCS treatment (fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined whether the observed effect of BGT226 is due to its inhibitory activity against ATM or mTOR/PI3K. We compared the effect of BGT226 with another PI3K/mTOR inhibitor VS-5584 that has similar or stronger effect in inhibiting PI3K and mTOR but no inhibition against ATM ( 37 ). We found that BGT226 but not VS-5584 sensitizes growth inhibition of cancer cells in response to NCS treatment (fig.…”
Section: Resultsmentioning
confidence: 99%
“…SuissADME platform [13] offers the synthetic accessibility coefficient of the proposed drug candidates. A compound is straightforward to synthesize if its coefficient is equal to 1 and very difficult to synthesize if this coefficient is equal to 10 [14] …”
Section: Resultsmentioning
confidence: 99%
“…A compound is straightforward to synthesize if its coefficient is equal to 1 and very difficult to synthesize if this coefficient is equal to 10. [14] Using Lipinski and Veber's rules, the similarity descriptors to the selected drugs were calculated with SwissADME.…”
Section: Synthetic Accessibility and Rules Of Lipinski And Vebermentioning
confidence: 99%
“…mTOR drug discovery mTOR is a compelling drug target, with recent advances garnering increasing attention. 34,64,[83][84][85][86] Beyond fundamental therapeutic indices such as solubility, affinity, and broad kinase toxicity with off-target effects, ensuring high selectivity for mTORC1 over mTORC2 is critical. mTORC2 inhibition has been associated with compromised insulin sensitivity and glucose intolerance.…”
Section: Activation Mechanism Of Mtor By Nrd Releasementioning
confidence: 99%